The Determinants of Economic Growth: An Empirical Investigation of North Carolina - Nwala, Kingsley (International Journal of Economics and Financial Issues, 2018)
This paper examines the determinants of economic growth in North Carolina using Autoregressive Distributed lag (ARDL) model approach, Co-integration, and Bounds tests. The state’s gross domestic product, gross investment, labor force, literacy rate, and foreign direct investments data were estimated. The bounds test revealed that all of the variables in the models are co-integrated, meaning that they have long-run relationships with economic growth of the state. The estimated coefficients are statistically significant at 5% level, and have the expected positive signs. Gross investment, labor force, literacy rate and foreign direct investments variables are strong determinants of economic growth in the state of North Carolina. The implications from the study are that government policies encouraging increased gross investment spending, lowering unemployment rate of the labor force, encouraging inflow of foreign direct investments, and increasing investments in human capital should be strongly pursued by the state policy makers. Keywords: North Carolina, Cointegration, Autoregressive Distributed lag (ARDL) modeling and Economic growth. JEL Classifications: E21, C23, C52